Management of Streptococcus pyogenes Preseptal Cellulitis in Multisystem Inflammatory Syndrome in Children (MISC): Poster Presentation - Case Report - Resident - ANAK AGUNG DEWI ADNYA SWARI; N.K. Niti Susila; I Gusti Ayu Made Juliari; Ida Ayu Ary Pramita (Majalah Oftalmologi Indonesia, 2023)
Introduction : Preseptal cellulitis were more common in children than adults. Preseptal cellulitis was an infection involving the anterior part of the orbita septum. Management of preseptal cellulitis, especially in children, were important to save visual function. Case Illustration : A boy, 1 year 8 months, was complained by his mother with swollen and redness on both eyes. The patient has a history of Multisystem Inflammatory Syndrome in Children (MISC) and Global Developmental Delay (GDD). Both eyes were edema, hyperemia, excoriation, bleeding, tenderness on eyelid, and conjunctival injection. Blood Culture examination results showed Streptococcus pyogenes bacteria. Patient was receiving therapy of antibiotics cefoperazone-sulbactam, amikacin, methylprednisolone intravena, enoxaparin subcutaneous injection, moxifloxacin and prednisolone asetat eye drops during hospitalization at Prof. Dr. I.G.N.G. Ngoerah General Hospital. Discussion : A patient with fever and respiratory tract infection was diagnosed with preseptal cellulitis. Preseptal cellulitis is a common infection of the eyelid and periorbita soft tissues characterized by acute eyelid erythema and edema. Antibiotic therapy had been started before blood culture examination. This study discusses toddler with preseptal cellulitis treated with antibiotics showing good results. ConclusionPreseptal cellulitis due tue multisystem inflammatory syndrome in children was an infection of the soft tissues of the eye that requires a multidisciplinary approach in management therapy. Early detection and adequate therapy have been proven to significantly improve patient survival rates and quality of life.